COVID 19: SEXUALITY AND ADAPTATION IN TIMES OF PANDEMIC - TABARA, MARIA PALACIOS; ROMERO, GLORIA TORRES; MACIAS, JAIME ZAMBRANO; GOMEZ, MARCO CALLE; ESPAÑA, INGRID GURUMENDI; VALLEJO-LÓPEZ, ALIDA (International Journal of Research -GRANTHAALAYAH, 2020)
Man’s adaptability over time has allowed him to continue to populate the planet in ever-increasing numbers. Currently a coronavirus outbreak, SARS COV-2 is causing death and shock worldwide, due to its rapid spread, has paralyzed industries, commerce, tourism, production and the economy. In the history of mankind, various pandemics have produced high death rates worldwide. The survival of the population depends on several factors, both biological, social, psychological and also on the sexual and reproductive health of the man in his environment. Diseases caused by microscopic agents, bacteria, viruses, among others, that exist in the environment and that can be very aggressive. Plans to deal with these pathogens must be constantly updated, it is essential to assume a change of attitude regarding daily habits, adopting hygiene, food and sexual and reproductive health measures to avoid the spread of diseases and guarantee the survival of the human race. in the planet.